FACTORS INFLUENCING ENTREPRENEURIAL INTENTIONS MEDIATED BY ENTREPRENEURSHIP EDUCATION IN S1 MANAGEMENT STUDENTS OF TARUMANAGARA UNIVERSITY - Theodore Darren Tan; and Wijaya (International Journal of Application on Economics and Business, 2024)
This research was conducted with the aim to determine the effect of entrepreneurial self-efficacy, entrepreneurial motivation, family support on entrepreneurial intention mediated by entrepreneurial education in Undergraduate Management Students at Tarumanagara University. The method used in this research is descriptive quantitative. The author used 200 respondents as subjects in this study, all of whom were students of the management and business faculties for the 2019-2022 class year. The results of the data from this study were obtained from data collection which was distributed via Google form online. This study explains that: 1) Entrepreneurial Self-efficacy has a non-positive effect on Entrepreneurial Education, 2) Entrepreneurial Self-efficacy has a positive effect on Entrepreneurial Education, 3) Entrepreneurial Motivation has a positive effect on Entrepreneurial Intention, 4) Entrepreneurial Motivation has a positive influence on Entrepreneurial Education, 5) Family Support has a positive effect on Entrepreneurial Intention, 6) Family Support has a non-positive effect on Entrepreneurial Education, 7) Entrepreneurial Education has a positive effect on Entrepreneurial Intention, 8) Entrepreneurial Self-efficacy has a not positive effect and does not significant effect on Entrepreneurial Intention mediated by Entrepreneurial Education, 9) Entrepreneurial Motivation has a non-positive and not significant effect on Entrepreneurial Intention mediated by Entrepreneurial Education, 10) Family Support has a non-positive and not significant effect on Entrepreneurial Intention mediated by Entrepreneurial Education.